1991
DOI: 10.1136/hrt.66.5.364
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial bridges: morphological and functional aspects.

Abstract: Objective-To assess the arrangement of myocardial bridges.Design-A necropsy study of 90 consecutive hearts (56 male, 34 female).Results-Myocardial bridges, either single or multiple, were seen in 50 (55-6%) of the 90 hearts. The left anterior descending artery was the most commonly affected artery. Thirty five of the 50 hearts which contained in total 41 muscle bridges were dissected further with a magnifying glass. Two different types of muscle bridges could be identified. Thirty one of these 41 myocardial br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
187
6
11

Year Published

1997
1997
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(217 citation statements)
references
References 17 publications
13
187
6
11
Order By: Relevance
“…Its transient nature and the dynamics of the obstruction help the differential diagnosis of fixed coronary stenoses. The left ADA is the most commonly affected artery 15 and 100% of the patients in the present study presented the isolated form of left ADA involvement. However, other arteries can be involved, such as the left circumflex artery and the right coronary artery 4 .…”
Section: Discussionmentioning
confidence: 97%
“…Its transient nature and the dynamics of the obstruction help the differential diagnosis of fixed coronary stenoses. The left ADA is the most commonly affected artery 15 and 100% of the patients in the present study presented the isolated form of left ADA involvement. However, other arteries can be involved, such as the left circumflex artery and the right coronary artery 4 .…”
Section: Discussionmentioning
confidence: 97%
“…There is a large difference between the incidence of MBs observed in pathological series and coronary angiography series. [8][9][10] While the incidence in autopsy series has been reported to be 15% to 85%, 11) the angiographic incidence has been reported to be 0.5% to 2.5%. 12) Most of the bridges seen in pathological examinations are invisible with angiography because only the deep type of bridges may be apparent angiographically.…”
Section: Discussionmentioning
confidence: 99%
“…Channer et al 11 , after a consecutive review of 1,000 coronary angiographies, found an incidence of 1.4% for MB in the ADA. Autopsy studies have shown an incidence of MB as high as 85% 2,3 . The presence of MB, which is considered a benign condition, in the ADA would be protective because it prevents the development of significant atherosclerosis in the affected area 12 .…”
Section: Discussionmentioning
confidence: 99%